Transureteroureterostomy for non-urologic pelvic malignancy: A case report - Karaman, Kerem; Halis, Fikret; Kaan Mansiroglu, Cemalettin; Koyun, Bulent; Aziret, Mehmet; Ercan, Metin (Annals of Medical Research, 2021)
None